Мир лесных растений - Петров Владимир Владимирович (Человек и окружающая среда, 1978)
Экземпляры: КХ (20060612) / Инвентарный номер: 672772 / Сис.шифр: 43.42 / Авт.знак: П 30 / ГРНТИ: 68 / ББК: 43.425